9-4m=2m-3

Simple and best practice solution for 9-4m=2m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-4m=2m-3 equation:


Simplifying
9 + -4m = 2m + -3

Reorder the terms:
9 + -4m = -3 + 2m

Solving
9 + -4m = -3 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
9 + -4m + -2m = -3 + 2m + -2m

Combine like terms: -4m + -2m = -6m
9 + -6m = -3 + 2m + -2m

Combine like terms: 2m + -2m = 0
9 + -6m = -3 + 0
9 + -6m = -3

Add '-9' to each side of the equation.
9 + -9 + -6m = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -6m = -3 + -9
-6m = -3 + -9

Combine like terms: -3 + -9 = -12
-6m = -12

Divide each side by '-6'.
m = 2

Simplifying
m = 2

See similar equations:

| Y=2(0+3)(0-4) | | 4y-23=10+y | | 23+13x-15+5x-27x= | | 14000V=-2000t+20000 | | 5(9a)= | | 14000V=-2000+20000 | | -10x+14-8x+9= | | 3x-4(1-2x)=2x-(x+1) | | 2(a-b)= | | 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 | | 4p-17.0=53.00 |

Equations solver categories